IMPLEMENTATION OF VIRTUAL REALITY IN LEARNING PRACTICE OF ANATOMY AND PHYSIOLOGY OF THE HUMAN BODY IN THE DEPARTMENT PHYSIOTHERAPY POLTEKKES KEMENKES JAKARTA III - Mustikasari, Nina; Lina, Ratu Karel; Devina, Christina Natalia (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
The development of information and communication technology, especially Virtual Reality (VR), has a significant impact on medical education. Previous research has indicated the effectiveness of VR in enhancing students' understanding. This study focuses on the implementation of VR in practical anatomy and physiology learning in Indonesia, aiming to investigate its effects on students' interest, enthusiasm, and understanding. The research adopts a quantitative descriptive approach with total sampling involving 51 respondents, first-semester students of the Applied Physiotherapy Bachelor's Program at Poltekkes Kemenkes Jakarta III. Research instruments include questionnaires, observation sheets via Google Form, and documentation. Data are analyzed using univariate analysis, bivariate analysis with chi-square tests, and multivariate analysis with multiple linear regression. The study reveals a significant relationship between interest and enthusiasm in using VR and the understanding of anatomy and human physiology learning. Interest and enthusiasm in learning with VR positively contribute to students' understanding. Based on the research findings, the use of VR in anatomy and physiology education at Poltekkes Kemenkes Jakarta III has a positive impact on students' interest, enthusiasm, and understanding. It is recommended to continue integrating VR into teaching, ensuring the availability of adequate devices. The use of VR is not limited to anatomy and physiology subjects but can be expanded to other subjects in the medical education curriculum. This study is expected to provide guidance and new insights in developing effective and innovative teaching methods in the future.